(9×7 +5)×10:2-(2+2×20:4×3+213:3)=
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
(9×7+5)×10:2-(2+2×20:4×3+213:3)=
(63+5)×10:2-(2+2×5×3+71)=
68×10:2-(2+10×3+71)=
68×5-(2+30+71)=
340-(32+71)=
340-103=237
Sper că te-am ajutat!
yourhelper087:
coroniță?
Răspuns de
0
(63+5)×10:2-(2+2×5×3+71)
68×10:2-(2+10×3+71)
68×10:2-(2+30+71)
68×10:2-(2+101)
68×10:2-103
68×5-103
204-103
101
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă